2017
DOI: 10.1021/acs.est.6b05928
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Comparison of Emission Factors, Number Size Distributions, and Morphology of Ultrafine Particles from 11 Different Household Cookstove-Fuel Systems

Abstract: Ultrafine particle (UFP) emissions and particle number size distributions (PNSD) are critical in the evaluation of air pollution impacts; however, data on UFP number emissions from cookstoves, which are a major source of many pollutants, are limited. In this study, 11 fuel-stove combinations covering a variety of fuels and different stoves are investigated for UFP emissions and PNSD. The combustion of LPG and alcohol (∼10 particles per useful energy delivered, particles/MJ), and kerosene (∼10 particles/MJ), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…Improved cookstoves, designed to improve fuel efficiency, have been distributed across the developing world. Improved cookstoves may have lower PM and CO emission factors (EF) compared to traditional stoves [13,14] The amount of fine particulate matter (PM2.5) associated with cooking is increasing in Africa and also is a problem in India and China [10][11][12][13][14][15]. The major fuels are charcoal as well as wood and although charcoal is widely available in urban areas, it is expensive and thus many rural areas mainly use firewood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved cookstoves, designed to improve fuel efficiency, have been distributed across the developing world. Improved cookstoves may have lower PM and CO emission factors (EF) compared to traditional stoves [13,14] The amount of fine particulate matter (PM2.5) associated with cooking is increasing in Africa and also is a problem in India and China [10][11][12][13][14][15]. The major fuels are charcoal as well as wood and although charcoal is widely available in urban areas, it is expensive and thus many rural areas mainly use firewood.…”
Section: Introductionmentioning
confidence: 99%
“…Rural areas predominately continue to use simple three stone fires, which can be made by the user. Generally the use of solid fuels for cooking in Africa has continued to increase alongside population growth [10] whilst in other areas, such as Europe it has tended to decline as shown Many studies have been made of the gaseous emissions [13,14] and efficiencies for a variety of cookstoves, but few studies have been made of PAH emissions especially to make comparisons between wood and charcoal fuels, although there has been a recent study of the PAH emissions of a range of biomass fuels as well as coal, but nit charcoal [12]. In this paper the emissions of PAH and some gaseous species are compared for wood and charcoal using an improved cookstove widely distributed in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…NO X and PM were related to traffic emissions [24,32], and most of the houses in Taiwan were adjacent to roads, so window opening might increase indoor NO 2 and PM 2.5 . For the influence of cooking, there were many simulated experiments exploring the air pollutant emissions of cooking-related fuel combustion [29,[33][34][35][36], and they demonstrated that CO, CO 2 , NO X , and PM 2.5 would be emitted by the process of the experiments. Although CO also was produced by cooking, it was revealed that combustion of high-grade fuels (such as natural gas, and LPG which contained propane, butane, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cooking activity requires a huge quantity of fuel. Similarly, the inefficient combustion increases the quantity of PM and CO emissions released in the air [22,23]. The insertion of the MA insert in a TSF or mud stove allows to lift the firewood off the ground and to ensure a constant air supply to the bottom.…”
Section: The Mewar Angithi Insert: Concept and Characteristicsmentioning
confidence: 99%